An Analysis of Public Information Disclosure in the Service Delivery of the West Sumatra Provincial Livestock and Animal Health Office - Fadillah Gusti Ardira; Nora Eka Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by the suboptimal implementation of public information disclosure at the Department of Animal Husbandry and Animal Health of West Sumatra Province, particularly in providing access to information through digital media. The study aims to analyze the implementation of public information disclosure in the agency's public services. This research employed a descriptive qualitative approach. The research subjects consisted of the Secretary of the Department, the Head of the General Affairs, Personnel and Finance Subdivision, a Senior Veterinary Officer, and members of the public selected through purposive sampling. Data were collected through observation, interviews, and documentation. The findings reveal that public information disclosure has generally been implemented well through direct services, social media, and the role of the Information and Documentation Management Officer (PPID). However, public access to information has not been fully optimized due to technical problems with the official website, limited updates of digital information, and the low utilization of information media by the public. Therefore, improvements in digital information management, inter-agency coordination, and public information services are necessary.